Adaptive Support Ventilation Attenuates Ventilator Induced Lung Injury: Human and Animal Study - Dai, Yu-Ling (Int J Mol Sci, 2019)
Adaptive support ventilation (ASV) is a closed-loop ventilation, which can make automatic adjustments in tidal volume (V(T)) and respiratory rate based on the minimal work of breathing. The purpose of this research was to study whether ASV can provide a protective ventilation pattern to decrease the risk of ventilator-induced lung injury in patients of acute respiratory distress syndrome (ARDS). In the clinical study, 15 ARDS patients were randomly allocated to an ASV group or a pressure-control ventilation (PCV) group. There was no significant difference in the mortality rate and respiratory parameters between these two groups, suggesting the feasible use of ASV in ARDS. In animal experiments of 18 piglets, the ASV group had a lower alveolar strain compared with the volume-control ventilation (VCV) group. The ASV group exhibited less lung injury and greater alveolar fluid clearance compared with the VCV group. Tissue analysis showed lower expression of matrix metalloproteinase 9 and higher expression of claudin-4 and occludin in the ASV group than in the VCV group. In conclusion, the ASV mode is capable of providing ventilation pattern fitting into the lung-protecting strategy; this study suggests that ASV mode may effectively reduce the risk or severity of ventilator-associated lung injury in animal models.